The Effectiveness of Interactive E-Modules in Evaluating OBE-Based History Learning through a Collaborative Team Project Approach - Arfan Diansyah; Yushar Tanjung; Syahrul Nizar Saragih; Abd. Haris Nasution (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study seeks to examine both the effectiveness and the practicality of an interactive e-module developed for the History Learning Evaluation course, which is grounded in the Outcome-Based Education (OBE) framework and employs a Team-Based Project approach. This development research follows the ADDIE model, consisting of five key phases: analysis, design, development, implementation, and evaluation. The research procedure began with a preliminary study and needs analysis, followed by the design of an e-module prototype. This prototype was then validated by subject-matter and media experts, trialed with students, and assessed for effectiveness through learning outcome tests. Data were gathered using questionnaires and tests, with subsequent analysis performed using descriptive quantitative methods. The results revealed that the interactive e-module attained a feasibility rating of 77% from material experts and 72% from media experts, both of which fall within the "feasible" category. In terms of effectiveness, the trial demonstrated a clear improvement in student performance, as evidenced by an increase in the average score from 63.13 on the pre-test to 79.46 on the post-test. Based on the predefined effectiveness criteria, the OBE-based interactive e-module with a Team-Based Project approach was officially deemed effective at enhancing student learning outcomes. In conclusion, this interactive e-module is considered both appropriate and effective for use as supplementary instructional material in the History Learning Evaluation course.